Perbedaan Tingkat Pemahaman Mahasiswa Bidang Keahlian Boga Lulusan SMA dan SMK Terhadap Istilah Asing Pada Materi Stock, Sauce, dan Appetizer - Mesha Oktariany Saraswati Millenia; Mariani Mariani; Guspri Devi Artanti (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This study aims to compare whether there are differences in levels of understanding between students graduates from Senior High School and Vocational High School about foreign terms in continental food processing subject especially stock, sauce, and appetizer. This research uses a descriptive comparative type of method. The number of samples in this research were 60 students with details 30 coming from students with vocational highschool background and 30 coming from students with senior high school background. The data were analyzed using an independent t-test. Based on the data, it can be found that the average value of understanding level about foreign terms of students from high school 16,96 and students who came from Vocational High School 20,90 and from these results, the highest average come from students with Vocational High School as the backgrounds. The results of testing the hypothesis by using independent sample t-test showed that the tcount is 3,378 where the ttable is less than 2,002 (α = 0,05) then Ho is rejected, and Ha is accepted. Based on the test results, it can be concluded that there is a significant difference between students graduated from Senior High School and students graduated from Vocational High School. From this study, it is recommended for cullinary students to seek more knowledge about foreign terms in continental food processing to enhance their competence and skill. For the study program, it is reccomends to gives more attention and to provide knowledge and learning about foreign terms especially those who have never received lessons in continental food processing.